2022
DOI: 10.1055/a-1936-3691
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Problematic Smartphone Use on Physical Activity Level and Musculoskeletal Pain

Abstract: Objectives The aim of this study was to examine the effects of problematic smartphone use on physical activity level and musculoskeletal pain. Methods Two hundred eighty university students (185 female; 95 male; mean age: 20.84±2.37 years) were included in the study. The International Physical Activity Questionnaire was used to determine the level of physical activity. Problematic smartphone use was determined using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In their investigation, Hao et al (2022) noted that academic burnout leads to more process smartphone use and indirectly generates more PSU. Unver & Buke (2022) found that PSU negatively impacts PA levels and exacerbates musculoskeletal pain. Such results all indicate that future experimental studies with stronger evidence are needed to test the intrinsic relationships between variables.…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation, Hao et al (2022) noted that academic burnout leads to more process smartphone use and indirectly generates more PSU. Unver & Buke (2022) found that PSU negatively impacts PA levels and exacerbates musculoskeletal pain. Such results all indicate that future experimental studies with stronger evidence are needed to test the intrinsic relationships between variables.…”
Section: Discussionmentioning
confidence: 99%